Biosorption of Cr VI supported on mordenite zeolite - Figueiredo, Hugo (2008)
This work reports the usage of a combined zeolite-biosorbent system for the removal and recovery of aqueous CrVI. The biosorption system consisted of a bacterium, Arthrobacter viscosus, supported on two mordenite (MOR) type zeolites with different Si/Al ratio, HMOR (Si/Al = 10) and NaMOR (Si/Al = 6.5). The results show that the biofilm of A. viscosus supported on MOR zeolite is able to recover chromium from dilute solutions. For both biosorption-MOR systems, the maximum removal was obtained for initial concentration of 20 mgCr/L. However, the best results were obtained for HMOR-system with a removal of 52.1 % for the diluted concentration and the best uptake, 3.3 mgCr VI/gzeolite, was achieved for the initial concentration of 100 mgCr/L. The Langmuir isotherm model was applied with good fitting to the experimental data.